2018
DOI: 10.1016/j.jpainsymman.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Role of U.S. Surgeons in the Provision of Palliative Care: A Systematic Review and Mixed-Methods Meta-Synthesis

Abstract: Among the articles reviewed, surgeons overall demonstrated insight into the benefits of palliative care but reported limited knowledge and comfort as well as a multitude of challenges to introducing palliative care to their patients. These findings indicate a need for wider implementation of strategies that allow optimal integration of palliative care with surgical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 66 publications
0
51
0
Order By: Relevance
“…Physician barriers include: decreased buy‐in and subsequent lack of referral to palliative care, desire to continue managing long‐term patients, and underexposure to the role and scope of palliative care in training . Additionally, many surgeons that do refer patients to palliative care report difficulties introducing these concepts to patients . Inherent to physician barriers are incomplete knowledge or inaccurate beliefs about the role and timing of palliative care, which is appropriate throughout the course of a potentially life‐limiting disease .…”
Section: Discussionmentioning
confidence: 99%
“…Physician barriers include: decreased buy‐in and subsequent lack of referral to palliative care, desire to continue managing long‐term patients, and underexposure to the role and scope of palliative care in training . Additionally, many surgeons that do refer patients to palliative care report difficulties introducing these concepts to patients . Inherent to physician barriers are incomplete knowledge or inaccurate beliefs about the role and timing of palliative care, which is appropriate throughout the course of a potentially life‐limiting disease .…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to interview physicians who do not include IPCC in their daily practice for their reasons in a further study, including a focus on different specialties, since surgical disciplines are underrepresented. Interestingly there is data, which shows that surgical specialties experience less education in palliative care and therefore feel uncomfortable addressing it [51]. The interviews were conducted in a rather long period of time (19 interviews in 17 months); so that there could be a change of interviewees' perception of IPCC additional to a maybe adjusted established practice in their daily work concerning PC patients.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Some of our participants experienced the first information about their incurable disease as delayed, insufficient, given in an inappropriate way or at an inappropriate place. This indicates that there is a need for increased focus on communication by HCPs both during their university studies and in hospitals 8. Furthermore, it would be desirable for surgeons to have more time allocated to conveying information and communicating with patients.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs also need to be aware of how much information each patient prefers and discuss this with the patient. Previous studies have shown that this awareness is associated with years of practice and confidence 8 10. Treatment and care of patients undergoing palliative chemotherapy should be organised in such a way that patients are able to see the same well-qualified physician and optionally also the same nurses at each consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation